Analisis Manajemen Rantai Pasok Sayuran Kangkung Hidroponik RH Farm Bogor - Siti Fatimah Azzahra; Mahayu Mawar Kalista; Farhana Talida Kamila; Salma Habiba Sabrine; Farid Afwan Firdaus (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
RH Farm is a hydroponic agribusiness that focuses on water spinach as the main commodity and is a regular supplier for Kluwih restaurants and several direct consumers. The research was conducted to find out how the supply chain activities for water spinach vegetable products in the RH Farm hydroponic business and the effectiveness of the supply chain being implemented. Researchers will analyze the overview and risk factors of the entire supply chain. The analytical method used is descriptive analysis with House of Risk (HOR) and Aggregate Potential Risk (APR). Based on the research results, the main factor influencing supply chain activities in the RH Farm hydroponic business was the lack of effective communication between workers with an APR value of 216 with an occurrence value of 9, a severity value of 8, and a risk correlation value of 3.